Faktor yang Mempengaruhi Penggunaan E-Peruncitan di Selangor - Azri, Ahmad Fariz; Wan Ahmad, Wan Nurul Karimah (Research in Management of Technology and Business, 2020)
E-grocery was created around the 1980s and began to be accepted in areas such as Europe, Australia, and Asia. E-grocery started in Malaysia around the year 2000. However, it still does not win the hearts of consumers in Malaysia. This study is to examine the factors that influence the use of e-grocery among consumers in the state of Selangor. The factors that have been studied are factors that encourage and prevent the use of e-grocery. This is a quantitative study using questionnaire method. Convenience sampling method was used by randomly selecting users in Selangor. Data has been analyzed using descriptive statistics to identify the factors that influence the use of e-grocery. The findings of this study show that cost factors, time, and user safety and privacy are the dominant factors that can influence the use of e-groceries, which is supported by previous studies.